Fabrication & characterization of thin film hybrid solar cell application - Chan, Yi Qi (2017)
Photovoltaics is one embodiment of solar energy where we convert sunlight into electricity. In photovoltaic panels, you have two leads coming out, basically, the equivalent of positive and negative terminal. The cells convert sunlight into electricity. Photovoltaics is the most widespread solar conversion technology today. In a society that is trying to go green and improve the world through renewable energy, solar energy and related materials becoming increasing important. In this project, we aimed to optimise the way of fabricating and characterising solar cell using thin films and hybrid organic/inorganic materials such as PEDOT: PSS, Molybdenum oxide (MoOx) and Indium tin oxide (ITO) which are categorised under transition metal oxide(TMO). In this report, we focused on Si- TMO solar cell. We fabricated 4 Si-TMO and 4 Si-PEDOT:PSS cells with varying thickness of the Si wafers. The thickness of Si wafers used are 675 µm, 40 µm, 20 µm and 10 µm, using the same doping concentration of 1015cm-3. The efficiencies of the Si-TMO cells are as follows: 675 µm 12.0%, 40 µm 6.3%,10 µm 2.4% and 20 µm 1.1%. On the other hand, the efficiencies of the Si-PEDOT:PSS are as follows: 675 µm 9.7%, 40 µm 4.2%, 10 µm 4.2% and 20 µm 3.2%. We found out that the 20 µm of Si-TMO solar cell, 20 µm and 10 µm of the Si-PEDOT:PSS solar cells were damaged with cracks within the cell during the characterization process. Further research and laboratory testing should be carried out to improve efficiency of the cells while reducing their cost.